2022
DOI: 10.1186/s12879-022-07828-y
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow assay (LFA) in the diagnosis of COVID-19-associated pulmonary aspergillosis (CAPA): a single-center experience

Abstract: Background Invasive pulmonary aspergillosis (IPA) is seen during coronavirus-2019 (COVID-19), has been reported in different incidences, and is defined as COVID-19-associated pulmonary aspergillosis (CAPA). Detection of galactomannan antigen is an important diagnostic step in diagnosing IPA. Enzyme-linked immunoassay (ELISA) is the most frequently used method, and lateral flow assay (LFA) is increasingly used with high sensitivity and specificity for rapid diagnosis. The present study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Among these studies, 20 were duplicates or targeted patients, five were non-human studies, and 10 studies did not report data of interest. Ultimately, 19 articles [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] were analyzed following eligibility assessment ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, 20 were duplicates or targeted patients, five were non-human studies, and 10 studies did not report data of interest. Ultimately, 19 articles [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] were analyzed following eligibility assessment ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the LFA method is sensitive and specific, and it can potentially be used as a diagnostic tool for SNP genotyping, which is associated with disease and has an impact on pharmacogenomics. However, LFA is more useful in diagnosing genetic diseases with homogeneous variants, such as thalassemia disease, and for infectious diseases such as COVID-19 ( 36 ), although a systematic review analysis based on preliminary data and pre-print papers has reported that the performance of the LFA has dropped with regard to the newer SARS-CoV-2 variants, the omicron variant, when compared to previous delta variant due to manufacturer dependent and lower viral loads in asymptomatic individuals ( 37 ). For diseases with heterogeneous variants, several techniques, such as whole exome sequencing and targeted sequencing, could be used to identify the variant and subsequent analysis using LFA for the family member can be done ( 34 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…[89][90][91] Several studies have investigated the use of LFTs in CAPA patients on serum and BALF (and TA), which showed good accordance with GM on the same samples. [92][93][94][95] In summary, bronchoscopy-based diagnostics remain the mainstay for diagnosis of VAPA.…”
Section: Different Patient Populations With Different Needs and Possi...mentioning
confidence: 99%